2021
DOI: 10.1016/j.heliyon.2021.e07622
|View full text |Cite
|
Sign up to set email alerts
|

Understanding gender issues in Nigeria: the imperative for sustainable development

Abstract: Whenever the term "Gender" is mentioned, many readily attribute it to the womenfolk who, in many societies, are challenged and often put in a disadvantaged position concerning the men. As a result, many women empowerment programs are being championed to cushion the effects of this subjugation on women. This paper attempts to look into gender and understand what has been in existence concerning gender roles, especially for females, and how it contributes to development. It is also important to note that develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…This could be attributed to the fact that more women are involved in organizing and being a part of community-based organizations throughout Nigeria [ 59 – 61 ] wherein there is easy access to information gathering and sharing. This concurred with the study by the Department of Gender and Social Development in which Olonade et al [ 63 ] found that more women form and join organizations nationwide. Furthermore, joining JBHI was higher among those with secondary education level and higher.…”
Section: Discussionsupporting
confidence: 88%
“…This could be attributed to the fact that more women are involved in organizing and being a part of community-based organizations throughout Nigeria [ 59 – 61 ] wherein there is easy access to information gathering and sharing. This concurred with the study by the Department of Gender and Social Development in which Olonade et al [ 63 ] found that more women form and join organizations nationwide. Furthermore, joining JBHI was higher among those with secondary education level and higher.…”
Section: Discussionsupporting
confidence: 88%
“…This has inadequately accounted for the importance of community-level factors that interventions could target not only for promoting women’s sexual health, but also for reducing the burden of adverse reproductive health outcomes among women in the country. It is particularly important to identify community-level predictors in Nigeria because of the persistence of communal cultural beliefs, gender norms and practices [ 31 , 32 ] that subjugate women’s sexual lives and general well-being to men’s control and authority. More often than not, the patriarchal system in Nigerian communities supports men’s dominance of power relations within households [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Olonade et al [17], Prayitno et al [18] and Chalongvorachai and Woraratpanya [19] and formed the theoretical basis of the research.…”
Section: Literature Reviewmentioning
confidence: 99%